The Sahabat Haramain Library as A Socially Inclusive Library in Enhancing Community Literacy - Fuady, Muhammad Thoyyib; Endang Danial; Susan Fitriasari (Mataram University, 2024)
A social inclusion-based library plays a crucial role in national development by enhancing community literacy. This research aims to first, identify the programs of Perpustakaan Sahabat Haramain in improving community literacy, and second, determine the key factors in enhancing community literacy. The approach used in this study is qualitative, utilizing a case study research method. Data collection techniques include interviews, observations, and documentation. The data analysis technique employed in this study follows Miles and Huberman's model, which consists of three steps: data reduction, data presentation, and conclusion drawing. The results of the research indicate that, first, through various programs, Perpustakaan Sahabat Haramain provides continuous and sustainable literacy education and training, thus broadening the community's knowledge. Second, the success factors in improving community literacy can be achieved through the collaboration of various parties, including the environment, parents, government, and the community. Support from all these elements is key to creating a positive and supportive environment for the sustainability of activities aimed at improving community literacy.